Bridging effect of recombinant human mannose-binding lectin in macrophage phagocytosis of Escherichia coli - Shiratsuchi, Akiko (Blackwell Science Inc, 2008)
Mannose-binding lectin (MBL) exists in the serum as a complex with MBL-associated serine protease (MASP). A recent paper described how MASP-free recombinant rat MBL stimulates the phagocytosis of Escherichia coli and Staphylococcus aureus by rat Kupffer cells through an increase in the level of a phagocytosis receptor. We have examined the effect of human MBL on the phagocytic action of human macrophages. Purified recombinant human MBL stimulated the phagocytosis of E. coli by THP-1 macrophages, leaving that of latex beads, apoptotic human cells, zymosan particles or S. aureus unchanged. This stimulatory effect was observed when either phagocytes or targets were preincubated with MBL. Furthermore, MBL bound to THP-1 macrophages as well as to E. coli, but not to S. aureus, through lipid A. These results indicated that human MBL in the absence of MASP stimulates macrophage phagocytosis of E. coli by bridging targets and phagocytes.